Book Review - Julien Chaisse (ed), China's International Investment Strategy: Bilateral, Regional, and Global Law and Policy, Oxford University Press, 2019 - Jusoh,Sufian (2019)
This text aims at commenting Julien Chaisse's book on China's international investment strategy, acknowledging that it presents a ground breaking approach and a wealth of thought-inspiring insights into the transformation and systemic impact of China's international investment rule-making and participation in investor-state arbitration. Indeed, the mentioned work will be able to assist, under the Belt and Road Initiative (BRI), professionals, policy makers and other interested parties to comprehend the impact of China's investments on the regional and global legal framework.